2015
DOI: 10.1016/j.breast.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and practice characteristics of pathologists who enjoy breast tissue interpretation

Abstract: Summary Physician attributes, job satisfaction and confidence in clinical skills are associated with enhanced performance and better patient outcomes. We surveyed 252 pathologists to evaluate associations between enjoyment of breast pathology, demographic/clinical characteristics and diagnostic performance. Diagnostic performance was determined by agreement with patient cases previously reviewed by a panel of experienced pathologists. Eighty-three percent of study participants reported enjoying breast patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A similar study on enjoyment of breast pathology interpretation also found no association with diagnostic performance but did similarly identify number of cases interpreted per week as statistically significantly associated with enjoyment [21]. It is likely that indicators of caseload volume and training or experience have an impact on job satisfaction and diagnostic accuracy owing to the resulting increase in skill and confidence.…”
Section: Discussionmentioning
confidence: 92%
“…A similar study on enjoyment of breast pathology interpretation also found no association with diagnostic performance but did similarly identify number of cases interpreted per week as statistically significantly associated with enjoyment [21]. It is likely that indicators of caseload volume and training or experience have an impact on job satisfaction and diagnostic accuracy owing to the resulting increase in skill and confidence.…”
Section: Discussionmentioning
confidence: 92%